The effect of miR-138 on the proliferation and apoptosis of breast cancer cells through the NF-κB/VEGF signaling pathway: Effect of miR-138 on breast cancer cells - Cheng, Hongbing; Chen, Liangji; Fang, Zhenyu; Wan, Qian; Du, Zhuo; Ma, Nanshan; Guo, Genxin; Lu, Wenjing (Cellular and Molecular Biology, 2022)
The analyze the effect of miR-138 on the proliferation and apoptosis of breast cancer cells through the NF-κB/VEGF signaling pathway is the Objective of this experiment. For this aim, the endometrial stem breast cancer cell line MCF-7 was cultured in vitro, and the overexpression mimic miR-138 mimics and the inhibitor anti-miR-138 were transfected into the endometrial stem breast cancer cell line MCF-7, which was set to overexpress miR-138 group and interfere with miR-138, and set up negative control of overexpression and negative control of inhibitor. Observe the cell proliferation and apoptosis ability of each group, and the changes in tumor necrosis factor-α (TNF-α), interleukin 1β, 6, 18 (IL-1β, IL-6, IL-18) levels, and compare the Bax of each group, NF-κB, VEGF protein expression level. Results showed that the proliferation ability of the miR-138 overexpression group was significantly lower than that of the miR-138 overexpression control group (P<0.05); the proliferation ability of the miR-138 interference group was significantly higher than that of the miR-138 interference control group (P<0.05). The apoptosis rate, caspase-3 and caspase-9 expression levels of the miR-138 overexpression group were significantly higher than those of the miR-138 overexpression control group (P<0.05); the apoptosis rate, caspase-3 and caspase-9 expression levels of the miR-138 interference group were significantly lower than those of the miR-138 interference control group (P<0.05). The expression levels of IL-1 β, IL-6, IL-18 and TNF - α in the miR-138 overexpression group were significantly lower than those in the miR-138 overexpression control group (P < 0.05). The protein expression levels of Bax, NF-κB and VEGF in the miR-138 overexpression group were significantly lower than those in the miR-138 overexpression control group (P < 0.05); the protein expression levels of Bax, NF-κB and VEGF in the miR-138 interference group were significantly higher than those in the miR-138 interference control group (P <0.05). The proliferation ability of the miR-138 overexpression group was significantly lower than that of the miR-138 overexpression control group (P < 0.05); the proliferation ability of the miR-138 + NF-κB overexpression group was significantly higher than that of the miR-138 overexpression group (P<0.05). The apoptosis rate of the miR-138 + NF-κB overexpression group was significantly lower than that of the miR-138 overexpression group (P < 0.05). Then MiR-138 can significantly inhibit the proliferation of breast cancer cells, promote apoptosis, and regulate the expression of inflammatory factors in the cells. It is speculated that the related mechanism may be related to the negative regulation of the NF-κB/VEGF signaling pathway.